Penguatan Profil Pelajar Pancasila melalui Pelatihan Penggunaan Tumbuhan sebagai Pewarna Alami Tenun Kebat Dayak Iban - Putra, Zakarias Aria Widyatama; Sulistyarini, Sulistyarini; Efriani, Efriani; Dewantara, Jagad Aditya; Olendo, Yudhistira Oscar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
To realise an evolved Indonesia that is self-sufficient and has a personality, the education vision begins with organising P5 as an integrated aspect of the Merdeka Curriculum. The Pancasila Student Profile Strengthening Project (P5) will give opportunity for students to enhance their character via learning experiences in the surrounding environment. This workshop aims to achieve the same purpose as Indonesian education: to provide students and elementary school children with hands-on experience using plants as natural dyes for Dayak Iban Kebat Weaving in Sungai Utik. The purpose of this activity is to preserve and protect Dayak Iban culture, particularly through the weaving method. The training technique employs a contextual approach, combining demonstration and practice. The lecturer was a Kebat weaving practitioner, and the training participants consisted of five youngsters from Sungai Utik. The assessment instrument utilised was a questionnaire completed by youngsters about their understanding of the usage of plants as natural colours. The instruction resulted in the 5 participants being able to use engkerbai laut, engkerbai kayo’ and renggat kikat plants as natural dyes for weaving yarn in the colours red and navy blue. They learnt the natural dyeing process firsthand by observing, selecting, sifting, and removing the boiling water to obtain colours suitable for use on woven yarns. This training is vital for improving P5, as it allows children to be actively involved in learning about and experiencing the natural dyeing process, which at the very least strengthens character and individuality while also providing cultural preservation space.